141. Implementation of Veterans Affairs Outpatient Antimicrobial Stewardship Interventions for Asymptomatic Bacteriuria and Acute Respiratory Infections, a Stepped Wedge Randomized Study - Mortrude, Grace (Open Forum Infect Dis, 2020)
BACKGROUND: Outpatient antimicrobial prescribing is an important target for antimicrobial stewardship (AMS) interventions to decrease antimicrobial resistance in the United States. The objective of this study was to design, implement and evaluate the impact of AMS interventions focused on asymptomatic bacteriuria (ASB) and acute respiratory infections (ARIs) in the outpatient setting. METHODS: This randomized, stepped-wedge trial evaluated the impact of educational interventions to providers on adult patients presenting to primary care (PC) clinics for ARIs and ASB from 10/1/19 to 1/31/20. Data was collected by retrospective chart review. An antibiotic prescribing report card was provided to PC providers, then an educational session was delivered at each PC clinic. Patient education materials were distributed to PC clinics. Interventions were made in a step-wise (figure 1) fashion. The primary outcome was percentage of overall antibiotic prescriptions as a composite of prescriptions for ASB, acute bronchitis, upper-respiratory infection otherwise unspecified, uncomplicated sinusitis, and uncomplicated pharyngitis. Secondary outcomes included individual components of the primary outcome, a composite safety endpoint of related hospital, emergency department or primary care visit within 4 weeks, antibiotic appropriateness, and patient satisfaction surveys. Figure 1 [Image: see text] RESULTS: There were 887 patients included for analysis (405 pre-intervention, 482 post-intervention). Baseline characteristics are summarized in table 1. After controlling for type 1 error using a Bonferroni correction the primary outcome was not significantly different between groups (56% vs 49%). There was a statistically significant decrease in prescriptions for bronchitis (20.99% vs 12.66%; p=0.0003). Appropriateness of prescriptions for sinusitis (OR 4.96; CI 1.79–13.75; p=0.0021) and pharyngitis (OR 5.36; CI 1.93 – 14.90; p=0.0013) was improved in the post-intervention group. The composite safety outcome and patient satisfaction survey ratings did not differ between groups. Table 1 [Image: see text] CONCLUSION: Multifaceted educational interventions targeting providers can improve antibiotic prescribing for indications rarely requiring antimicrobials without increasing re-visit or patient satisfaction surveys. DISCLOSURES: All Authors: No reported disclosures